(untitled) (Discourse of Law and Administration, 2023)
The article aims to advocate for respecting the rights to privacy and autonomy of individuals who express intentions to commit suicide, necessitating medical and police intervention. Drawing upon materials presented by the police on July 20, 2023, and the ruling of the District Court for Kraków Krowodrza, in Kraków, 2nd Criminal Division, with reference number II Kp 589/23/K, the analysis is centered around the “Kraków Case” of April 28, 2023.